The systems work of social change : how to harness connection, context, and power to cultivate deep and enduring change - Schweer Rayner, Cynthia; Bonnici, François (Tantor Media, Inc., 2022)
The issues of poverty, inequality, racial injustice, and climate change have never been more pressing or paralyzing. Current approaches to social change, which rely on linear thinking and traditional power dynamics to "solve" social problems, are not helping. In fact, they may only be entrenching the status quo. Systemic social challenges produce bewildering results when we try to solve them due to their complexity, scale, and depth. While strategies to tackle complexity and scale have received significant attention and investment, challenges that arise from deeply-held beliefs, values, and assumptions that no longer serve us well have been largely overlooked. This book draws on stories of committed social changemakers to uncover a set of principles and practices for social change that dramatically depart from the industrial approach. Rather than delivering solutions or being lured by grander visions of "systems change," these principles and practices focus on the process of change itself. Simple yet profound, these stories distill a timely set of lessons for leaders, scholars, and policymakers on how connection, context, and power sit at the heart of the change process, ensuring broader agency for people and communities while building social systems that are responsive in a rapidly-changing world